A challenging red eye clinical quiz - Derrick Smit (South African Family Practice)
The following red eye cases and this clinical quiz is not only aimed at over the counter (OTC) medication, but also illustrates the importance of referring patients who do not respond to OTC medicines or primary medical attention. The case studies are discussed in more detail after the initial case presentations. Read the case studies and decide whether the causes are bacterial, viral, or allergic and decide what treatment you would have prescribed for the patient, or if you would refer the patient.